Classic magic tricks - Longe, Bob; Knoles, David; Townsend, Charles Barry (New York : Main Street, 2003)
Virtually every type of incredible magic trick you can imagine is here in this huge collection. Try anything you find inside and astound people with your great repertoire. Use mental magic to mystify a crowd with your uncanny mathematical talent. Defy reality by performing the French Drop. Create suspense when you make a 'spirited' handkerchief rise and fall. And more!
Includes index.
84635
Keywords: Magic tricks. -- Sleight of hand. -- Juvenile Literature